2008
DOI: 10.1259/bjr/65306248
|View full text |Cite
|
Sign up to set email alerts
|

Treatment results of boron neutron capture therapy using intra-arterial administration of boron compounds for recurrent head and neck cancer

Abstract: The effect of boron neutron capture therapy (BNCT) is correlated with the density of boron in the tumour. BNCT using intra-arterial administration of boron compounds was performed for recurrent head and neck cancer. Of the five patients treated, one achieved a complete response and four achieved a partial response. There was one case of transient headache but no severe adverse effects were observed. The advantages of using an intra-arterial administration route for BNCT, which causes the selective killing of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Results from a few small series (11)(12)(13) and case reports (14,15) suggest that BNCT is effective in the treatment of locally recurrent head-and-neck cancer, and that most tumors respond to BNCT.…”
Section: Introductionmentioning
confidence: 99%
“…Results from a few small series (11)(12)(13) and case reports (14,15) suggest that BNCT is effective in the treatment of locally recurrent head-and-neck cancer, and that most tumors respond to BNCT.…”
Section: Introductionmentioning
confidence: 99%
“…[16] BNCT is mainly used for the treatment of malignant brain tumors, malignant melanoma and head and neck cancers (HNC), especially for tumors that are difficult to treat by conventional methods such as surgical resection, chemotherapy and radiotherapy. [17][18][19][20][21][22] The cyclooxygenase-2 (COX-2), one of the two isoforms of COX, is usually rarely expressed inmost normal tissues but rapidly inducedunder pathological conditions suchas inflammation and cancers. [23] The expression of COX-2 has been reported to be increased in many cancers, including head and neck cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that BNCT is an effective treatment for inoperable, locally recurrent head and neck cancer. Most patients who receive prior radiotherapy with X-rays or gamma rays respond to BNCT [6][7][8].…”
Section: Introductionmentioning
confidence: 99%